Indian Interests and Evolving Policies under BJP Leadership: Projections for 2024 - Nidaa Shahid (CISS Insight Journal, 2022)
The Modi government, following its 2014 election win, pursued a set of policies outlined by the 2014 BJP election manifesto. The policies included stronger Indo-US relations, ingress in the Indo-Pacific, military equipment and nuclear material deals with various countries, aggressive regional postures, and most importantly projection of India as a lucrative market. Following the election, the newly elected government tried but failed to entice the global investors through economic incentives. The 2019 BJP manifesto likewise identified a number of interests and policies, which the Modi government followed once it was re-elected. These included hyper-nationalism and xenophobia centred on Hindutva; abrogation of Article 370; continued regional hegemonic designs in Indo-Pacific region; modernisations in conventional, nuclear, outer space and emerging technologies domains, besides increasing reliance on hybrid warfare. The resulting Indian aggression following these hard-line policies has the potential to stir domestic turmoil, and affect regional instability. Following past trends, it seems likely that 2024 BJP manifesto would be more domestic/ inward looking with the foreign policy component being showcased as an augmentation of domestic agenda. Regional bellicosity would likely continue under the guise of India attaining its rightful status of a great power. The international collaborations in the military domain are likely to grow. If re-elected, an even more aggressive Modi is likely to emerge with greater focus on the RSS ideology.